SOURCES ON THE HISTORY OF THE FOREIGN MOVEMENT IN KHORASAN AND MOVAROUNNAHR AND THEIR ANALYSIS - Azimova Iroda Homidjon qizi (Sciental Journals Publishing, 2025)
This article analyzes Arabic and Persian sources related to the history of the Kharijite movement-a major religious-political force that played a significant role in the political struggles in Khurasan and Transoxiana during the 8th–9th centuries. The study particularly examines sources such as al-Tabari’s History of the Prophets and Kings (Tarikh al-Rusul wa al-Muluk), al-Baladhuri’s Futuh al-Buldan, Ibn Aʿtham al-Kufi’s Kitab al-Futuh, al-Ya‘qubi’s Tarikh, and others.
Keywords: Kharijites, Khurasan and Transoxiana, Asad ibn Abdallah al-Qushayri, Kharith ibn Surayj, Tarikh-i Seistan, Tarikh al-Rusul wa al-Muluk, Futuh al-Buldan, Kitab al-Futuh, Tarikh, Nasr ibn Sayyar, Hamza the Kharijite.